Unusual cause of gastrointestinal bleeding: Grönblad-Strandberg syndrome - Kildušis, Edvinas; Kedikas, Renatas; Afanasjev, Andrej; Brimas, Gintautas (Lietuvos chirurgija, 2025)
Grönblad-Strandberg syndrome (also referred as pseudoxanthoma elasticum) is a rare genetic metabolic disease, causing ectopic calcification of organism elastic fibers. This leads to vascular complications including bleeding. Hemorrhages from various organs and tissues are reported, but gastrointestinal bleeding is particularly common. We managed a 55-year-old man rich in comorbidities with acute severe gastrointestinal bleeding in the stomach. Despite the unclear cause of the bleeding at the time emergency endoscopy was made, during which the bleeding was completely stopped and patient’s hemodynamics was stabilized. To prevent recurrent bleeding in the future transcatheter vascular embolization was performed. The clip placed during endoscopy helped the interventional radiologist select the correct vessels for embolization. Only after detailed and strict anamnesis later the diagnosis was established. After 5 years period the patient is still alive and active despise wide and severe adjacent pathology without episodes of recurrent bleeding. Clinicians must keep in mind rare genetic disorders that may cause the gastrointestinal bleeding and evolve diagnostic and management complex to achieve clinical success.
Keywords: Grönblad-Strandberg syndrome; pseudoxanthoma elasticum; gastrointestinal bleeding; unusual cause; genetic disease; endoscopy; angiography; diagnostic; embolization; surgery